Overcoming Severe Food Insecurity in Central Java Province of Indonesia Amidst Covid-19 Pandemic - Yusuf Munandar (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2020)
To overcome the problem of the severe food insecurity in the Central Java Province of Indonesia amidst the Covid-19 outbreak, the Indonesian government provided staple foods assistance to them. The research question is whether the provision of staple foods assistance will overcome the problem of severe food insecurity in Central Java Province of Indonesia? The purpose of this study was to determine whether the provision of staple foods assistance would overcome the problem of severe food insecurity in Central Java Province of Indonesia. This research method is a descriptive analysis using 2019 Susenas data obtained from BPS Indonesia. The result of the study is that the provision of staple foods assistance can not overcome the problem of severe food insecurity in Central Java Province of Indonesia because it is based on DTKS data and local government data which only covers 54.69% of all residents of Central Java Province who suffer from severe food insecurity. The recommendation of this research is the Indonesian central and local government so as to update DTKS data and local government data as soon as possible so that DTKS data and local government data can include all residents of Central Java Province who suffer from severe food insecurity so that they no longer suffer from severe food insecurity.